2020
DOI: 10.1002/1878-0261.12641
|View full text |Cite
|
Sign up to set email alerts
|

NEK2 induces autophagy‐mediated bortezomib resistance by stabilizing Beclin‐1 in multiple myeloma

Abstract: NEK2 is associated with drug resistance in multiple cancers. Our previous studies indicated that high NEK2 confers inferior survival in multiple myeloma (MM); thus, a better understanding of the mechanisms by which NEK2 induces drug resistance in MM is required. In this study, we discovered that NEK2 enhances MM cell autophagy, and a combination of autophagy inhibitor chloroquine (CQ) and chemotherapeutic bortezomib (BTZ) significantly prevents NEK2‐induced drug resistance in MM cells. Interestingly, NEK2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 47 publications
(62 reference statements)
2
64
0
Order By: Relevance
“…Autophagy is activated by the assembly of a complex of NEK2/USP7/Beclin-1 in MM cells. Indeed, treatment with a combination of the autophagy inhibitor chloroquine (CQ) and the chemotherapeutic bortezomib (BTZ) significantly prevents NEK2-induced drug resistance in MM cells [156]. The efficacy of fluorouracil (FU) in the treatment of colorectal cancer (CRC) is greatly limited by drug resistance.…”
Section: The Pivotal Role Of Ulk In the Development Of Drug Resistancmentioning
confidence: 99%
“…Autophagy is activated by the assembly of a complex of NEK2/USP7/Beclin-1 in MM cells. Indeed, treatment with a combination of the autophagy inhibitor chloroquine (CQ) and the chemotherapeutic bortezomib (BTZ) significantly prevents NEK2-induced drug resistance in MM cells [156]. The efficacy of fluorouracil (FU) in the treatment of colorectal cancer (CRC) is greatly limited by drug resistance.…”
Section: The Pivotal Role Of Ulk In the Development Of Drug Resistancmentioning
confidence: 99%
“…Although NEK2 expression is upregulated in various cancers, the regulation of its expression remains unclear. Studies have shown that USP7 deubiquitinates NEK2 and affects its stability 13 . We therefore examined whether USP7 deubiquitinated NEK2 and affected its function in PAs, and confirmed a specific interaction between USP7 and NEK2 in transiently transfected HEK293T cells using co-immunoprecipitation (Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…It can pass through the BBB and is widely used for the treatment of glioma 21 . However, long-term application is likely to induce acquired drug resistance, and drug resistance is still one of the problems that cannot be ignored in the treatment of tumors 22 . In high-throughput sequencing results, we found that hsa_circ_0110757 of Mcl-1 was overexpressed in TMZ-resistant glioma patient tissues and cells.…”
Section: Discussionmentioning
confidence: 99%